Índice de sustentabilidade aplicado à Bacia do Rio Cuiá-João Pessoa(PB) - Reis, André Luiz Queiroga (2010)
Currently there is a need for the development and application of techniques for environmental monitoring and provide data showing reliable, practical and easy to obtain the main spheres of public and population inserted in a given ecosystem. One such technique is the application of Sustainability Indexes, they combine qualitative and quantitative aspects of social, environmental, economic and institutional. This way quality of water and other natural resources in a watershed become the main environmental indicators related to sustainability and can be influenced by many factors relacioned by the biotic, physics and social environment. The relations between biotic and abiotic environment make up part of a sensible balance, which is why change in this relations in the hydrographic basin can alter its quality. Develop one or more indexes that better represent the trend of environmental sustainability, providing warning information to society and the government and therefore propose conservation actions in the Cuiá hydrographic basin, according to the Local Agenda 21, forms the main structure of this work. Were used as indicators of the four dimensions of sustainability (social, environmental, economic and institutional) to form the index of sustainability applied specifically in the hydrographic basin of Cuiá river in João Pessoa. The methodology for assessing the trend of sustainability of the basin was based on the Dashboard Sustainability. This system or method is proposed mainly by four stages: 1 - Identify reference information and specific relevance of the study area, thereby gathering the primary data, since each 2-Analyze primary and make the analysis parameters, 3 - Evaluate the performance of each parameter to compose the indicator of each dimension of sustainability, and 4 - Add performance indicators to compose the Tendency of Sustainability Index Trend in the study area. The conclusion in this work that was possible context and discuss the theoretical concepts of sustainability and propose the use of a methodology to operationalize these concepts from the Dashboard Sustainability and still propose actions that promote actions to improvement of the sustainability index. The results obtained by the research revealed the fragility of an urban socioecosystemic, like the Cuiá hydrographic basin, where the high degree of urbanization without proper planning continuously deteriorating environmental conditions, and reflects the greater need of government and society work in an integrated way in environmental conservation, social equity and economic development.